The (many) afterlives of transitional justice: practice-based insights on continuity, impact and evolving justice struggles - Destrooper, Tine (International journal of transitional justice, 2025)
In the past decade, the paradigm of transitional justice has come under increasing scrutiny. Transitional justice scholarship has been characterized by self-reflective critiques, while on the ground even emblematic transitional justice cases have seen the (re)emergence of authoritarian tendencies, raising further questions about the paradigm’s legitimacy. Yet, in practice, a wide range of (grassroots) justice actors continue to invoke transitional justice as a mobilizing framework and action repertoire in an increasingly wide range of long and encompassing struggles for justice. These seemingly contradictory dynamics of crisis and expansion raise the question of how transitional justice lives on, both in a temporal and conceptual sense, years to decades after its initial deployment, and in the face of new socio-political and legal dynamics. This article builds on eight focus groups with 69 local justice actors from seven countries to present practitioner-informed insights about the many afterlives of transitional justice. Based on qualitative thematic analysis, we argue that these afterlives are shaped by plural, co-existing dynamics of continuity and ongoingness, unfolding through novel initiatives and processes across varying timelines, driven by the protagonism of victim-survivors, civil society and youth. This temporal stretching led practitioners to highlight the significance of intergenerational initiatives and impacts, to resituate the perceived legacies of early and standardized transitional justice interventions within protracted and evolving justice trajectories and to underscore the importance of the communicative functions and potential of transitional justice language and tools to bolster new and intersecting justice struggles.